TEACHING DESCRIPTIVE TEXT IN AN INDONESIAN EFL CONTEXT: TEACHER STRATEGIES AND CLASSROOM CHALLENGES - Dhiya Salsabila; Munir Munir; Chaerul Fadlan Saud (State University of Makassar, 2026)
This study aimed to explore the strategies used by an English teacher in teaching descriptive text and the challenges encountered during their implementation at SMA IT Al-Ishlah Maros. Employing a descriptive qualitative design, the study involved one English teacher selected through purposive sampling. Data were collected through classroom observations, semi-structured interviews, and documentation, and analyzed using Miles and Huberman’s interactive model. The findings revealed that the teacher integrated the Genre-Based Approach (GBA) and Discovery Learning, supported by modeling, scaffolding, collaborative learning, and visual media to facilitate students’ understanding of descriptive text. Despite these strategies, the teacher encountered several challenges, including students’ low motivation, limited vocabulary, grammatical difficulties, mixed-ability classrooms, and limited instructional time. The study concludes that integrating structured and student-centered approaches can effectively support the teaching of descriptive text while highlighting the importance of teachers’ pedagogical flexibility in responding to diverse classroom needs. The findings provide practical insights for English teachers seeking to improve descriptive writing instruction in similar EFL contexts.Keywords: Descriptive text, Discovery Learning, Genre-Based Approach, Teacher Strategies, Writing instruction.